Paisagem, modelos urbanísticos e as áreas habitacionais de primeira e segunda residência - Macedo, Silvio Soares (Paisagem e Ambiente, 1998)
This paper focuses the relationship between the traditional urban pattern of green neighbourhoods and the ocupation of the coastal zone by residential touristics areas and this efects over the primitive landscape